PENGARUH TELECTRONIC BANKING PADA PERBANKAN DI INDONESIA - FAIRUZ FIRJATULLAH; UMMI ITIAH NST; WILDA EFRILYATI DAULAY; NURBAITI, NURBAITI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
This research focuses on the advancement of communication networks that continue to develop in Indonesia, the development of information technology has brought many fundamental changes to the life of modern society, providing great convenience and assistance to people's work. In this study, subjective techniques with examination and exploration strategies are used to obtain information about banking businesses that use the internet as a medium to obtain transactions and other information through the bank's website. Internet banking features include general information about savings/current accounts, savings accounts, account transition information, money transfers between banks and others. To access internet banking, we must have a user ID by registering with the bank. We can perform various banking transactions according to the banking features available on internet banking without us having to go to the bank or to an ATM machine to transact. Even so, in internet banking there are also risks that we must anticipate and avoid. Transact carefully and don't be fooled by the many scams out there, especially those that target the people in the banking world.